Takhrij and Syarah Hadith of Agrotechnology: Study of Cultivation by Hydroponics Method - Putri Mufadila; Wahyudin Darmalaksana; Amalia Purdianty (Gunung Djati Conference Series, 2021)
This study aims to discuss the hadith with regard to hydroponics. This research method is a qualitative type through literature study and field studies with the takhrij and sharah hadith approaches. The results and discussion of this research is that hydroponics is a modification of the plant cultivation management system, but the drawback of hydroponic cultivation is that it requires expensive investment and requires special skills in maintenance. The conclusion of this research is the takhrij and syarah hadith of the Prophet about hydroponics is a plant cultivation that can be done in a narrow area.